Partisipasi Stakeholder dalam Pengembangan Kurikulum Pendidikan Islam di Pesantren - Muh Ibnu Sholeh; Muhammad Fathurro’uf; Sokip Sokip; Asrop Syafi’i; Nur ’Azah; Dwi Andayani (Edu Journal Innovation in Learning and Education, 2023)
This research aims to analyze the obstacles and challenges in involving stakeholders in developing the Islamic education curriculum in Islamic boarding schools, how stakeholders contribute to each stage of the curriculum development process and recommendations for Islamic boarding schools and educational development policies related to the Islamic education curriculum in Islamic boarding schools. The method used in this research is the library research method, data was obtained from various sources such as scientific journals, books, seminar papers and other publications both offline and online. The data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. The research results show that obstacles and challenges that may arise include differences in views and priorities, limited time and resources, inequality of representation, technical challenges, politics and personal interests, lack of effective communication, resistance to change, and intimidation of results. Stakeholders contribute to each stage of the curriculum development process by identifying needs and objectives, designing materials and learning, selecting learning and evaluation methods, testing and assessing, and revising and adjusting. Recommendations for Islamic boarding schools and educational policies related to curriculum development include increasing stakeholder involvement, forming a curriculum development team, openness to innovation, and integrating religious values. For education policy, apart from support and recognition, development of training stakeholders, provision of resources, support for research and innovation and partnerships with Islamic boarding schools.